Implementation of Canva Based Interactive Learning Media Using AI PROMPT to Increase Students' Learning Interest in the Material 'Hello It’s My Pet' for Grade 1 Elementary School English Subject - Syal Sa Billa Intan Romadona; Endang Noerhartati; Vica Alverina Auria Santoso; Siti Azizah; Tjatursari Widiartin; Noviana Desiningrum (Universitas Pendidikan Ganesha, 2026)
Students’ low interest in learning English is caused by the use of conventional teaching methods and the lack of interactive and engaging learning media. This study aims to analyze the effectiveness of Canva based interactive learning media supported by PROMPT AI in improving students’ learning interest and learning outcomes on the topic of pet introduction in English learning. This research uses a descriptive qualitative approach involving 21 students as research subjects. Data collection techniques include observation, in depth interviews with teachers and students, and documentation of learning activities. Research instruments consist of observation guidelines, interview guidelines, and documentation sheets. Data were analyzed using triangulation techniques to ensure data validity through comparison of multiple sources. The results show that Canva-based learning media with PROMPT AI creates a more interactive, enjoyable, and meaningful learning environment. Students demonstrate increased engagement, motivation, and understanding of the learning material. Quantitative results indicate a significant improvement, where the average pretest score of 52% increased to 98.75% in the posttest, showing a learning improvement of 46.75%. This study concludes that Canva-based interactive media effectively improves the quality of English learning in elementary schools. Teachers can use Canva to create creative, engaging, student-centered, and technology-based learning.